DISKRESI PENEGAK HUKUM DALAM PENERAPAN PREJUDICIEEL GESCHIL - Marleno, Risma; Rumihin, Ony Frengky; Arwanto, Bambang (Jurnal HUKUM BISNIS, 2025)
Law enforcement discretion is an essential instrument in judicial practice that provides flexibility for judges or law enforcement officials to make decisions based on juridical, moral, and propriety considerations, outside of rigid legal provisions. One of its strategic applications is in prejudicieel geschil, which is a mechanism to postpone the examination of criminal cases until there is a civil case decision that has a substantial relationship with the subject matter of the criminal case, which aims to prevent contradictions in decisions between courts. This mechanism is regulated in Supreme Court Regulation Number 1 of 1956 and Supreme Court Circular Letter Number 4 of 1980, which distinguishes two forms of prejudicieel geschil, namely question pre judicielles a l action (mandatory delay) and question prejudicielles au judgement (facultative delay). Based on normative legal research with a statute approach and conceptual approach. Keywords: Discretion, Law Enforcement, Prejudicieel Geschil